2005
DOI: 10.1021/jm0491896
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Neutral and Zwitterionic 3-Carboranyl Thymidine Analogues for Boron Neutron Capture Therapy

Abstract: Novel 3-carboranyl thymidine analogues (3CTAs) were synthesized as potential boron delivery agents for boron neutron capture therapy (BNCT). This library includes six zwitterionic NH(3)(+)-nido-m-carborane-substituted thymidine analogues (Thds) and the corresponding neutral NH(2)-closo-m-carborane-substituted counterparts. All compounds of this library were good substrates for recombinant human thymidine kinase 1 (TK1) with phosphorylation rates up to 89% relative to that of Thd. One compound out of this libra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 52 publications
6
63
1
Order By: Relevance
“…[55] This has also been suggested as the major internalization route for carboranethymidine derivatives reported by Tjarks and colleagues. [56] Sufficient cell uptake of Re/Tc-labeled dThd complexes remains an obstacle that prevents their application in diagnosis and therapy at this point.…”
Section: Discussionmentioning
confidence: 99%
“…[55] This has also been suggested as the major internalization route for carboranethymidine derivatives reported by Tjarks and colleagues. [56] Sufficient cell uptake of Re/Tc-labeled dThd complexes remains an obstacle that prevents their application in diagnosis and therapy at this point.…”
Section: Discussionmentioning
confidence: 99%
“…28 Yields in this step were 80% for 6 and 85% for 7, respectively. Basic hydrolysis of the benzoate esters 6 and 7 produced 8 and 9 in 92% and 95% yields, respectively.…”
Section: Introductionmentioning
confidence: 95%
“…19,20 The nucleoside analogues radiolabeled in the 3 0 -position reported to date are 3 Recently a series of N-3(substituted)thymidine analogues carrying a carborane moiety at the N-3-position with various spacer length have drawn attention in boron neutron capture therapy. [24][25][26][27][28] It has been reported that some of the N-3(substituted)thymidine analogues are phosphorylated by TK1 with 50-89% efficiency as compared to thymidine, while being poor substrates for thymidine phosphorylase. [25][26][27] Furthermore, some simple N-3(substituted)thymidine derivatives such as ethyl, n-butyl, acetylenic, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The first step is the simulation of the 3CTAs crossing of the membrane, which occurs by passive diffusion Byun et al, 2005). Free energy approaches such as metadynamics (Laio and Parrinello, 2002) could be used.…”
Section: Perspectivesmentioning
confidence: 99%